Diseño de un cd interactivo, de música nacional tradicional, empleando la ilustración, para rescatar la identidad cultural, en los estudiantes de la unidad académica de ciencias de la ingeniería y aplicadas, perteneciente a la Universidad Técnica de Cotopaxi, en la ciudad de Latacunga, en el período 2014 - Carpio Asimbaya, Juan Carlos (2015)
Cultural Identity is a set of beliefs, ways of thinking, customs and values inculcated from generation to generation, the same ones that have been getting lost through the time. Every day, globalization has spread all over the world, seizing young people who are more susceptible to be influenced by new musical styles, whether in culture and traditional. Since time ago, to the present day, youth imitates in order to feel one way or another accepted in society, which effect is the own loss about cultural identity. Music is the culture that enlivens the awakening of people; it is it is the essence for the development of the world; therefore, music is an essential part of humanity. Through music and culture, it identifies a village which has been left aside by the lack of diffusion in mass media. In spite of being established in the article 103 of the Law of Communications, it orders that produced, composed and executed music in Ecuador, it must represent at least 50 % of musical content broadcast in all its schedules, with the payment of copyright, as established by law. This isn‟t fulfilled and a few hours presented do it in hours in which the young people don‟t tune in a radio station, as it has been stated.